Containers, genres, and formats, oh my: Creating sustainable concepts by connecting theory, research, practice, and education. Issue 1 (22nd October 2020) - Brannon, Brittany; Valenza, Joyce; Cataldo, Tara T.; Kear, Robin; Faniel, Ixchel
Abstract: This interactive panel brings together researchers, practitioners, and educators to explore ways of connecting theory, research, practice, and LIS education around the issue of information format. Despite a growing awareness of the importance of information format to information seeking, discovery, use, and creation, LIS has no sound, theoretically‐informed basis for describing or discussing elements of format, with researchers and practitioners alike relying on know‐it‐when‐they‐see‐it understandings of format types. The Researching Students' Information Choices project has attempted to address this issue by developing the concept of containers, one element of format, and locating it within a descriptive taxonomy of other format elements based on well‐established theories from the field of Rhetorical Genre Studies. This panel will discuss how this concept was developed and implemented in a multi‐institutional, IMLS‐grant‐funded research project and how panelists are currently deploying and planning to deploy this concept in their own practice. Closing the loop in this way creates sustainable concepts that build a stronger field overall.